2023
DOI: 10.1021/acs.joc.2c02302
|View full text |Cite
|
Sign up to set email alerts
|

External Electric Field Induces a Mechanistic Crossover in the Reactivity of 1,3-Dienes with Sulfur Dioxide: Sulfolene Versus Sultine

Abstract: 1,3-Dienes (1) react with SO 2 to produce sulfolenes (2) and sultines (3). Previous experiments and computational studies have shown that hetero-Diels−Alder (HDA) reaction producing the sultine is kinetically favorable compared to the chelotropic (CE) reaction producing the sulfolene. In this article, DFT calculations for a series of substituted 1,3-dienes show that under the influence of a moderate oriented external electric field (OEEF) of 2.0−4.0 V nm −1 along the reaction axis, the chelotropic reaction bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…That is, the change of NICS(0) values due to the introduction of substituting groups comes from the sum of the change of individual groups. For doubly substituted derivatives, it follows eqn (10), and for triply substituted benzoic acids, eqn (11) is Table 3 Statistical analysis results of the fitted pK a values using the additivity effect for doubly and triply cyano-substituted benzoic acid derivatives under external electric field along x-and y-axes, including correlation coefficient R 2 , mean squared error (MSE), root-mean-square error (RMSE), and mean absolute error (MAE) between the calculated and fitted pK a values…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the change of NICS(0) values due to the introduction of substituting groups comes from the sum of the change of individual groups. For doubly substituted derivatives, it follows eqn (10), and for triply substituted benzoic acids, eqn (11) is Table 3 Statistical analysis results of the fitted pK a values using the additivity effect for doubly and triply cyano-substituted benzoic acid derivatives under external electric field along x-and y-axes, including correlation coefficient R 2 , mean squared error (MSE), root-mean-square error (RMSE), and mean absolute error (MAE) between the calculated and fitted pK a values…”
Section: Resultsmentioning
confidence: 99%
“…From eqn ( 7)- (11), we can see that different properties for multiply substituted species might follow different additivity rules. This difference is dictated by the nature of the concerned properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The experimental difficulty in using external electric field (EEF) lies with the fact that one needs to fix the electric field along the reactant coordinates in a reaction mixture. [21][22][23][24][25] To this end, there are a few experimental studies which have shown that, via the use of a scanning tunnelling microscopy (STM) tip and gold surface, 19,20 the direction of an external electric field can be controlled in a real experiment. 19,20,23,26 In the present work we have explored the possibility of using an EEF as a catalyst increasing the efficiency of an aryl amination reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve such a goal, introducing an oriented external electric field (OEEF) could be a suitable way. By enhancing the intermolecular charge transfer (CT) in transition states (TSs), the OEEF along the reaction axis can effectively reduce the activation barrier and catalyze the [4 + 2] cycloaddition, which has been detected in experiments supported by the STM technology. Moreover, by utilizing the directional response of an electric field to the dipole orientation of reactants, theoretical investigations by Shaik and co-workers proposed that a 100% R/S enantioselectivity in DA reactions can be achieved. Accordingly, the OEEF is expected to not only enhance the reactivity but also promote the selectivity of products. In particular, although the dipole moments of I h _symmetric C 60 and D 5 h _symmetric C 70 are vanishing, the monoadducts are polarized with the inherent dipoles pointing from the electron-accepting carbon cages to the indene motif acting as the electron donor. According to the principles of molecular electrostatics, it can be deduced that the monoadducts should be oriented along with the dipole vector under OEEFs, and therefore, we are expecting that those different sites on the fullerene monoadduct can be selectively activated or passivated to generate highly regioselective bisadducts that cannot be achieved using traditional chemical approaches.…”
Section: Introductionmentioning
confidence: 99%